2020
DOI: 10.3390/antiox9090856
|View full text |Cite
|
Sign up to set email alerts
|

Maternal N-Acetylcysteine Therapy Prevents Hypertension in Spontaneously Hypertensive Rat Offspring: Implications of Hydrogen Sulfide-Generating Pathway and Gut Microbiota

Abstract: Hypertension can come from early life. N-acetylcysteine (NAC), a hydrogen sulfide (H2S) precursor as well as an antioxidant, has antihypertensive effect. We investigated whether maternal NAC therapy can protect spontaneously hypertensive rats (SHR) male offspring against hypertension. The pregnant rats were assigned to four groups: SHRs without treatment; Wistar Kyoto (WKY) without treatment; SHR+NAC, SHRs received 1% NAC in drinking water throughout pregnancy and lactation; and, WKY+NAC, WKY rats received 1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 51 publications
2
48
1
Order By: Relevance
“…Interestingly, an animal study using a maternal suramin-induced programmed hypertension model demonstrated that maternal NAC treatment protected male rat offspring against hypertension, which was associated with an increased protein level of 3-MST and H 2 S synthesis in the kidney (92). Another rodent model showed similar results, this time involving NAC-induced enhancement of renal 3-MST and CBS (but not CSE) protein levels, as well as H 2 S-releasing activity in offspring kidneys of hypertensive mothers (44). Taurine is a metabolite of cysteine and strongly boosts the CSE enzyme, and thereby contributes to increase the endogenous H 2 S level in humans (90,114).…”
Section: Potential Enhancement Of Endogenous H 2 S Levelsmentioning
confidence: 85%
“…Interestingly, an animal study using a maternal suramin-induced programmed hypertension model demonstrated that maternal NAC treatment protected male rat offspring against hypertension, which was associated with an increased protein level of 3-MST and H 2 S synthesis in the kidney (92). Another rodent model showed similar results, this time involving NAC-induced enhancement of renal 3-MST and CBS (but not CSE) protein levels, as well as H 2 S-releasing activity in offspring kidneys of hypertensive mothers (44). Taurine is a metabolite of cysteine and strongly boosts the CSE enzyme, and thereby contributes to increase the endogenous H 2 S level in humans (90,114).…”
Section: Potential Enhancement Of Endogenous H 2 S Levelsmentioning
confidence: 85%
“…Conversely, approaches including probiotics, prebiotics, postbiotics (e.g., SCFAs), or microbial inhibitors that target specific pathways (e.g., TMAO), have shown beneficial cardiovascular effects [121]. Our previous research demonstrated that supplementation with prebiotic inulin, probiotics Lactobacillus casei, or postbiotics acetate during pregnancy and lactation can protect adult offspring against hypertension programmed by a variety of maternal insults [122][123][124].…”
Section: Gut Microbiota Dysbiosismentioning
confidence: 99%
“…We confined this review to antioxidants implemented mainly during gestation and lactation which are critical periods for kidney development. As listed in Table 2 , we summarize current knowledge on perinatal use of antioxidants used as a reprogramming strategy to protect offspring against renal programming in various animal models [ 29 , 30 , 31 , 33 , 34 , 35 , 36 , 59 , 60 , 62 , 63 , 67 , 70 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. As the DOHaD research is a flourishing field, this list is likely to grow rapidly.…”
Section: Targeting Oxidative Stress By Antioxidants As a Reprogrammentioning
confidence: 99%
“…In the prenatal dexamethasone and postnatal high-fat diet model, the beneficial effects of NAC against offspring hypertension were associated with increased H 2 S-generating enzyme expression, increased plasma glutathione level, and reduction of renal 8-OHdG expression [ 36 ]. In another study, perinatal use of NAC also protected SHR offspring against hypertension via increased expression and activity of renal H 2 S-generating enzymes and activity [ 97 ]. Furthermore, NAC therapy in pregnancy and lactation prevented hypertension programmed by maternal suramin administration, which coincided with increased GSH and restoration of NO [ 33 ].…”
Section: Targeting Oxidative Stress By Antioxidants As a Reprogrammentioning
confidence: 99%